Amorphous high ion conductivity cathode material and preparation method thereof and application in all-solid-state lithium-ion battery

Amorphous high-ion conduction positive electrode material was synthesized by high-energy ball milling method, and a cluster structure was generated by the halogen exchange reaction of FeOCl and LiF, which solved the problem of low ion conductivity of the positive electrode material in all-solid-state lithium-ion batteries, and achieved high rate performance and high energy density.

CN119315027BActive Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411834705.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In all-solid-state lithium-ion batteries, the ion conductivity of high-ion conductivity positive electrode materials is low, which affects its ion transmission network performance and rate performance under cold pressing conditions.

Method used

Amorphous high-ion conduction positive electrode material was synthesized by high-energy ball milling method, using FeOCl as the reactant, and a cluster structure based on F replaced octahedral FeO4Cl2-xFx was generated through a halogen exchange reaction to form an amorphous main phase.

Benefits of technology

This material has high room temperature ion conductivity and low ion transport activation energy under cold pressing conditions, which significantly improves its rate performance and cycle stability when used as a positive electrode material. It does not require the addition of a supporting electrolyte, and the proportion of positive electrode active substances can exceed 95% by weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315027B_ABST
    Figure CN119315027B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of all-solid-state lithium-ion battery positive electrode materials, and particularly relates to an amorphous high ion conductivity positive electrode material and a preparation method thereof and application in all-solid-state lithium-ion batteries. The chemical composition general formula of the positive electrode material is Li x FeOClF x , where 0.2
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium-ion batteries, and specifically relates to an amorphous high-ion-conductivity positive electrode material and a preparation method thereof, and an application thereof in all-solid-state lithium-ion batteries. Background Art

[0002] With the continuous improvement of the demand for electrification in modern society and the requirements of the "dual carbon" goal, the importance of electrochemical energy storage has become increasingly apparent. Among electrochemical energy storage, lithium-ion batteries occupy the vast majority of the market share due to their advantages of high energy density and good cycle performance. However, traditional lithium-ion batteries are currently facing two challenges: energy density approaching the theoretical limit (about 300 Wh / kg) and increasingly prominent battery safety issues, which makes it urgent to develop a new electrochemical energy storage system with both high energy density and high safety. On the basis of traditional liquid lithium-ion batteries, all-solid-state lithium batteries use non-flammable solid electrolytes, which greatly reduces the risk of thermal runaway of batteries; at the same time, solid electrolytes are conducive to inhibiting the growth of lithium dendrites on the lithium metal negative electrode during the cycle process, so that all-solid-state lithium batteries can match the lithium metal negative electrode, thereby greatly improving the energy density of the battery. Therefore, all-solid-state lithium-ion batteries are the current focus of lithium battery development.

[0003] At present, the ionic conductivity of solid electrolytes used in all-solid-state lithium-ion batteries has reached or even exceeded the level of liquid electrolytes. At the same time, the composite electrolyte strategy can obtain a wide voltage window to solve the problem of positive and negative electrode matching. Therefore, the multiphase contact problem between active materials, solid electrolytes, and battery additives in all-solid-state lithium batteries is currently the key problem restricting the development of all-solid-state lithium batteries. In recent years, a series of positive electrode materials with high ionic conductivity have emerged. Lithium ion transmission networks can be constructed under cold pressing conditions. When such materials are used to prepare composite positive electrodes, no additional supporting electrolytes can be added. While increasing the proportion of active materials in the composite positive electrode, the electrochemical performance loss caused by the interface contact problem between the positive electrode material and the supporting electrolyte is avoided, becoming a very promising solution to the multiphase interface contact problem of composite positive electrodes of all-solid-state lithium batteries. However, the high ionic conductivity positive electrode materials reported so far generally have problems such as low ionic conductivity and high ion transmission activation energy, which leads to poor performance in constructing ion transmission networks and affects the capacity and rate performance of positive electrode materials. Summary of the invention

[0004] In view of the above-mentioned technical problems, the present invention provides a high ion conductivity cathode material and a synthesis method and its application in all-solid-state lithium-ion batteries. The present invention synthesizes an amorphous high ion conductivity cathode material by high-energy ball milling, and the room temperature ion conductivity under cold pressing conditions reaches 0.1 mS cm -1level, and can be directly used as a composite positive electrode material in all-solid-state lithium-ion batteries after a simple composite with conductive carbon, with good cycle stability and rate performance. This material uses FeOCl with a two-dimensional layered structure as a reactant, and utilizes the halogen exchange reaction between halide materials to partially exchange the F in the LiF lithium source with the Cl in FeOCl through a high-energy ball milling reaction. Since Cl in FeOCl plays a bridging role in stabilizing the layered structure, and F cannot play a bridging role for Cl due to its smaller ion radius and higher charge density, after F replaces part of the Cl in FeOCl, the original two-dimensional layered structure collapses, and under the action of high-energy ball milling, octahedral FeO4Cl is produced with F replacing FeOCl. 2-x F x The amorphous phase is formed by a cluster structure based on the amorphous phase. Another reaction product is LiCl, which exists in the form of microcrystals. The amorphous property of the material enables it to conduct lithium ions isotropically, and the grain boundary-free property enables lithium ions to be transported at a high flux through percolation, effectively improving its ability to build an efficient ion transport network under cold pressing conditions, and significantly improving the room temperature ionic conductivity of the material and the rate performance when used as a positive electrode material. At the same time, the presence of active Fe sites in the material enables it to have the ability to reversibly deintercalate lithium ions, and can be used as a positive electrode material for all-solid-state lithium-ion batteries. When no supporting electrolyte is added, the content of positive electrode active substances can exceed 95 wt%, which significantly improves the energy density at the positive electrode level. In addition, since the synthetic raw material of the material is iron-based chloride with large crust reserves and low cost, and the synthesis process of the material only involves high-temperature calcination and high-energy ball milling without a protective gas atmosphere, the material has a strong cost advantage and industrial scale-up potential.

[0005] In order to achieve the above object, the technical solution of the present invention includes:

[0006] In the first aspect, the present invention provides an amorphous high ion conductive positive electrode material, wherein the positive electrode material is composed of five elements: lithium, iron, oxygen, chlorine, and fluorine, and the chemical composition formula is Li x FeOClF x , where x represents the molar ratio of Li and F relative to FeOCl, 0.1 <x<1。

[0007] More preferably, 0.125 <x<0.75。

[0008] In the second aspect, the present invention provides an application of an amorphous high ion conductivity positive electrode material, which is used in an all-solid-state lithium-ion battery, has high lithium ion conductivity and stable charge and discharge capabilities, and after being compounded with a conductive agent, can achieve stable operation in an all-solid-state lithium-ion battery at room temperature without adding a supporting electrolyte.

[0009] In a third aspect, the present invention provides a method for preparing an amorphous high ionic conductivity cathode material, the method comprising the following steps:

[0010] Step 1: Take FeCl3·6H2O or saturated FeCl3 aqueous solution and place it in a porcelain boat.

[0011] Step 2: Place the porcelain boat in a muffle furnace, heat it to 200 - 230 °C and keep it at this temperature for a period of time, then naturally cool it to room temperature.

[0012] There is no requirement for the atmosphere during the calcination process, and no protective gas atmosphere is needed.

[0013] Step 3: Grind the sample calcined in Step 2, wash it with a solvent and dry it to obtain the FeOCl intermediate.

[0014] Step 4: Mix the FeOCl intermediate obtained in Step 3 with LiF evenly.

[0015] Step 5: Add the mixture of the FeOCl intermediate and LiF in Step 4 into a ball milling jar, add ball milling beads into the jar, and then seal the ball milling jar for high-energy ball milling reaction.

[0016] Step 6: Grind the product obtained in Step 5 to obtain the amorphous high ionic conductivity cathode material.

[0017] Further, in Step 2, the heating rate is 3 - 5 °C / min and the holding time is 2 h.

[0018] In Step 3, the washing step includes two steps of water washing (preferably deionized water washing) and organic solvent washing, and the selected organic solvent is one or a mixture of two or more of methanol, ethanol, ether, and acetone.

[0019] In Step 5, the specific process of the high-energy ball milling reaction is that the ball milling speed is 300 - 2000 rpm, preferably 500 - 1000 rpm, and the ball milling reaction time is 5 - 10 h.

[0020] Further, in Step 4, LiF is used as the lithium source, FeOCl is used as the iron source, and the molar ratio of LiF to FeOCl is y, and 0.1 < y < 1, preferably 0.125 < y < 0.75.

[0021] In a fourth aspect, the present invention provides a composite cathode for an all-solid-state lithium-ion battery, comprising the amorphous high ionic conductivity cathode material and a conductive agent.

[0022] Further, the mass of the high ionic conductivity cathode material accounts for 90 - 95% of the total mass of the composite cathode.

[0023] Furthermore, the conductive agent is one or more of carbon nanotubes, carbon nanofibers, graphene, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5-10% of the total mass of the composite positive electrode.

[0024] In a fifth aspect, the present invention provides an all-solid-state lithium-ion battery, comprising the all-solid-state lithium-ion battery composite positive electrode.

[0025] Furthermore, the all-solid-state lithium-ion battery also includes a solid electrolyte and a negative electrode;

[0026] The solid electrolyte is a double-layer electrolyte composed of Li2ZrCl6 and Li6PS5Cl; the negative electrode is a lithium metal foil or a lithium indium alloy foil.

[0027] The beneficial effects of the present invention are:

[0028] The amorphous iron-based oxyhalide positive electrode material of the present invention only needs to be compounded with a small amount of conductive carbon to be applied to all-solid-state lithium-ion batteries, thereby increasing the proportion of active materials in the positive electrode to 95wt%.

[0029] (2) The amorphous iron-based oxyhalide cathode material of the present invention achieves high room temperature ionic conductivity and low ion transport activation energy through an amorphization strategy, which effectively improves its rate performance as a high ion conductivity cathode material.

[0030] (3) The amorphous iron-based oxyhalide cathode material of the present invention uses iron, which is a relatively abundant element in the earth's crust, as a raw material, and has a significant cost advantage over the currently reported high ion-conducting cathode materials that use high-priced transition metal elements.

[0031] (4) The synthesis process of the amorphous iron-based oxyhalide positive electrode material described in the present invention is simple, the material has good humidity stability, and has low requirements for a protective atmosphere during the synthesis process, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1;

[0033] Figure 2 is the X-ray diffraction spectrum of Example 1 and the FeOCl intermediate corresponding to Example 1;

[0034] Figure 3 The EIS spectra of Examples 1-4 and Comparative Examples 2-6 are shown;

[0035] Figure 4 The charge and discharge curves of the positive electrode materials prepared for Examples 1-4, Comparative Example 5 and Comparative Example 6 in all-solid-state lithium-ion batteries;

[0036] Figure 5 The cycle performance diagram of the positive electrode material prepared in Example 1 in an all-solid-state lithium-ion battery;

[0037] Figure 6 The rate performance diagram of the positive electrode material prepared for Example 1-4 in an all-solid-state lithium-ion battery;

[0038] Figure 7 The EIS spectra of Example 1 before and after the humidity resistance test;

[0039] Figure 8 The XRD spectra of Example 1 before and after the humidity resistance test are shown. DETAILED DESCRIPTION

[0040] Example 1

[0041] Synthesis of FeOCl intermediate: Weigh 3 g of FeCl3·6H2O and place it in a clean porcelain boat and spread it flat. Place the porcelain boat in a muffle furnace and set the heating rate to 3 °C / min. Raise the temperature to 200 °C and maintain for 1.5 h. Cool it down naturally to room temperature to obtain a dark purple solid. Grind it in a mortar and wash it once with deionized water and three times with anhydrous ethanol. Then, dry the washed powder in a vacuum at 80 °C overnight to obtain FeOCl intermediate powder.

[0042] Electrode material synthesis: Weigh 0.1079 g LiF and 0.8921 g FeOCl respectively and grind and mix them evenly with a mortar (corresponding to a reactant molar ratio of 0.5:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm:8 mm:5 mm=1:10:5, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it appropriately with a mortar until there is no obvious block (no agglomeration) to obtain an amorphous high ion conductive positive electrode material Example 1.

[0043] Preparation of halide electrolyte Li2ZrCl6: Weigh 0.2641 g LiCl and 0.7359 g ZrCl4 respectively and grind them in a mortar to mix evenly. Put the mixed sample into a ball mill, add 75 g of ball milling beads, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it in a mortar until there is no obvious block to obtain the halide electrolyte Li2ZrCl6.

[0044] The blocking electrode method measures the ionic conductivity of the material: Use a Beijing Zhongke Wanyuan two-electrode ionic conductivity test cell with an inner diameter of 10 mm, add 80 mg of positive electrode material powder, place it on a press and apply 4 tons of pressure for 2 min. The thickness of the battery before and after adding the positive electrode material powder is measured to calculate the thickness of the positive electrode material sheet. Connect the mold battery to the electrochemical workstation for EIS testing, apply a bias of 100 mV, and test the frequency range of 0.1~7 MHz.

[0045] Preparation of composite positive electrode: Weigh 190 mg of high ion conductive positive electrode material and 10 mg of Ketjen black respectively, grind with a mortar to mix the reactants evenly. Put the mixed sample into a zirconium dioxide ball mill, add 50 g of zirconium dioxide ball milling beads with different diameters in a ratio of 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 550 rpm for 4 h. Scrape the sample out of the ball mill to obtain a composite positive electrode material.

[0046] All-solid-state lithium-ion battery assembly: Use a Beijing Zhongke Wanyuan solid-state two-electrode pressure-controlled mold with an inner diameter of 10 mm, add 50 mg Li2ZrCl6 and 50 mgLi6PS5Cl (China Research Institute Technology Group Co., Ltd.), place it on a press and apply 1 t pressure for 1 min to prepare a composite electrolyte layer. Weigh 2 mg of composite positive electrode material, spread it evenly on one side of Li2ZrCl6, and then place it on a press and apply 4 t pressure for 2 min. Attach a 50μm thick lithium foil on one side of Li6PS5Cl. Maintain the operating pressure of 1 t for the entire battery, and perform constant current charge and discharge tests and rate tests.

[0047] Humidity stability experiment: Weigh 500 mg of amorphous high ion conductive cathode material and place it in a container. The container is opened and placed in a drying room with a temperature maintained at 25±1°C and a dew point temperature of -15±2°C for 12 h. The container is then sealed and transferred to a glove box, and samples are taken for ionic conductivity testing.

[0048] Example 2

[0049] Synthesis of FeOCl intermediate: Weigh 2 g of FeCl3 in a beaker, add 1 mL of deionized water and 1 mL of concentrated hydrochloric acid respectively, and ultrasonicate for more than 10 min until the solid is completely dissolved. Add broken porcelain pieces to the beaker to prevent violent boiling, place it in a vacuum drying oven and heat it to 95 °C for 10 min to obtain a saturated FeCl3 solution. Then place the beaker in a muffle furnace and set the heating rate to 3 °C / min, heat it to 200 °C and keep it for 1.5 h, cool it naturally to room temperature, and obtain a dark purple solid. After grinding it in a mortar, wash it once with deionized water and three times with anhydrous ethanol. Then, dry the washed powder at 80 °C in vacuum overnight to obtain FeOCl intermediate powder.

[0050] Electrode material synthesis: Weigh 0.1079 g LiF and 0.8921 g FeOCl respectively and grind and mix them evenly with a mortar (corresponding to a reactant molar ratio of 0.5:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm:8 mm:5 mm=1:10:5, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it appropriately with a mortar until there is no obvious block to obtain Example 2 of amorphous high ion conductive positive electrode material.

[0051] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0052] The preparation method of the composite positive electrode is the same as that of Example 1.

[0053] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0054] Example 3

[0055] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0056] Electrode material synthesis: Weigh 0.0578 g LiF and 0.9422 g FeOCl respectively and grind and mix them evenly with a mortar (corresponding to a reactant molar ratio of 0.25:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm:8 mm:5 mm=1:10:5, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it appropriately with a mortar until there is no obvious block to obtain Example 3 of amorphous high ion conductive positive electrode material.

[0057] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0058] The preparation method of the composite positive electrode is the same as that of Example 1.

[0059] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0060] Example 4

[0061] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0062] Electrode material synthesis: Weigh 0.1554 g LiF and 0.8446 g FeOCl respectively and grind them in a mortar to mix evenly (corresponding to a reactant molar ratio of 0.75:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm:8 mm:5 mm=1:10:5, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample out of the ball mill and grind it appropriately in a mortar until there is no obvious block to obtain amorphous high ion conductive positive electrode material Example 4.

[0063] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0064] The preparation method of the composite positive electrode is the same as that of Example 1.

[0065] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0066] Comparative Example 1

[0067] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0068] Electrode material synthesis: Weigh 1 g of FeOCl and put it into a ball mill, add 75 g of ball milling beads, where the ratio of the number of ball milling beads with different diameters is 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 1000 rpm for 8 h. Scrape the sample out of the ball mill to obtain a composite positive electrode comparative example 1.

[0069] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0070] The preparation method of the composite positive electrode is the same as that of Example 1.

[0071] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0072] Comparative Example 2

[0073] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0074] Electrode material synthesis: Weigh 0.1948 g LiF and 0.8052 g FeOCl respectively, grind with a mortar to mix the reactants evenly (corresponding to a reactant molar ratio of 1:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at a speed of 1000 rpm for 8 h. Scrape the sample out of the ball mill to obtain a composite positive electrode comparative example 2.

[0075] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0076] The preparation method of the composite positive electrode is the same as that of Example 1.

[0077] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0078] Comparative Example 3

[0079] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0080] Electrode material synthesis: Weigh 0.1079 g LiF and 0.8921 g FeOCl respectively, grind with a mortar to mix the reactants evenly (corresponding to a reactant molar ratio of 0.5:1). Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 1000 rpm for 2 h. Scrape the sample out of the ball mill to obtain a composite positive electrode comparative example 3.

[0081] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0082] The preparation method of the composite positive electrode is the same as that of Example 1.

[0083] Comparative Example 4

[0084] The synthesis method of FeOCl intermediate is the same as that in Example 1.

[0085] Electrode material synthesis: Weigh 0.1079 g LiF and 0.8921 g FeOCl respectively, grind with a mortar to mix the reactants evenly. Put the mixed sample into a ball mill, add 75 g of ball milling beads with different diameters in a ratio of 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 200 rpm for 8 h. Scrape the sample out of the ball mill to obtain composite positive electrode comparative example 4.

[0086] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0087] The preparation method of the composite positive electrode is the same as that of Example 1.

[0088] Comparative Example 5

[0089] Electrode material synthesis: Weigh 0.4476g LiCl and 0.5524g VCl3 respectively, grind with a mortar to mix the reactants evenly (corresponding to a reactant molar ratio of 3:1). Put the mixed sample into a ball mill, add 75g of ball milling beads with different diameters in a ratio of 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 1000 rpm for 8 h. Scrape the sample out of the ball mill to obtain a composite positive electrode comparative example 5.

[0090] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0091] The preparation method of the composite positive electrode is the same as that of Example 1.

[0092] Comparative Example 6

[0093] Electrode material synthesis: Weigh 0.4g LiCl and 0.6g FeCl2 respectively, grind with a mortar to mix the reactants evenly (corresponding to a reactant molar ratio of 2:1). Put the mixed sample into a ball mill, add 75g of ball milling beads with different diameters in a ratio of 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 1000 rpm for 8 h. Scrape the sample out of the ball mill to obtain a composite positive electrode comparative example 6.

[0094] The blocking electrode method for measuring the ionic conductivity of the material is the same as in Example 1.

[0095] The preparation method of the composite positive electrode is the same as that of Example 1.

[0096] The positive electrode material synthesis methods and some test results of Examples 1-4 and Comparative Examples 1-6 are summarized in Table 1:

[0097] Table 1: Cathode material synthesis method and some test results

[0098] phase of matter FeOCl precursor Ball milling conditions Ionic conductivity (mS / cm) Specific capacity (mAh / g) Example 1 <![CDATA[Li 0.5 FeOClF 0.5 ]]> Synthesis of Ferric Chloride Hexahydrate 1000rpm,8h 0.257 408.8 Example 2 <![CDATA[Li 0.5 FeOClF 0.5 ]]> Synthesis of saturated ferric chloride solution 1000rpm,8h 0.251 380.5 Example 3 <![CDATA[Li 0.25 FeOClF 0.25 ]]> Synthesis of Ferric Chloride Hexahydrate 1000rpm,8h 0.244 386.5 Example 4 <![CDATA[Li 0.75 FeOClF 0.75 ]]> Synthesis of Ferric Chloride Hexahydrate 1000rpm,8h 0.168 387.2 Comparative Example 1 FeOCl Synthesis of Ferric Chloride Hexahydrate 1000rpm,8h - - Comparative Example 2 LiFeOClF Synthesis of Ferric Chloride Hexahydrate 1000rpm,8h 0.009 - Comparative Example 3 <![CDATA[Li 0.5 FeOClF 0.5 ]]> Synthesis of Ferric Chloride Hexahydrate 1000rpm,2h 0.007 - Comparative Example 4 <![CDATA[Li 0.5 FeOClF 0.5 ]]> Synthesis of Ferric Chloride Hexahydrate 200rpm,8h 0.001 - Comparative Example 5 <![CDATA[Li3VCl6]]> - 1000rpm,8h 0.033 163.1 Comparative Example 6 <![CDATA[Li2FeCl4]]> - 1000rpm,8h 0.008 283.4

[0099] Experimental results analysis:

[0100] The scanning electron microscope (SEM) was used to characterize Example 1. Figure 1As shown in the SEM results, it can be seen that the sample particle size is 5~20 um; some microcrystalline grains are attached to the surface of the particles, which are LiCl microcrystals, one of the reaction products.

[0101] The FeOCl intermediate in Example 1 and the amorphous high ion conductive cathode material prepared in Example 1 were characterized by X-ray diffraction (XRD). Figure 2 As shown. The test results show that the FeOCl precursor after high-energy ball milling reaction with LiF is obviously amorphized. Except for the main phase of the amorphous phase, the microcrystalline components in the XRD spectrum are LiCl and Fe2O3, of which LiCl is a microcrystalline product generated by the reaction of LiF and FeOCl, and Fe2O3 comes from the partial decomposition of the FeOCl precursor during the high-energy ball milling reaction. The amorphous main phase plays the role of ion transport and lithium storage in the material. Since the amorphous material has an isotropic ion transport path, a more efficient and stable ion transport network can be constructed compared to the crystalline phase material, so that the ion conductivity is significantly improved, which is beneficial to improve the rate performance and cycle stability of the positive electrode material. It was determined by XRD and solid nuclear magnetic characterization that the crystalline phase content in Example 1 was about 15 mol%, and the crystalline phase content in Example 2 was about 17 mol%.

[0102] The positive electrode materials prepared in Examples 1-4 were characterized by ionic conductivity using the blocking electrode method. The results are as follows: Figure 3 The thickness of the positive electrode material layer after cold pressing in Examples 1-4 is 0.34 mm, 0.37 mm, 0.32 mm and 0.36 mm respectively. The Nyquist diagram is drawn according to the EIS test results, and the actual resistance value at the inflection point of the arc in the high-frequency region is read. The ionic conductivity is calculated to be 0.259 mS cm -1 , 0.254 mS cm -1 , 0.241 mS cm-1, 0.168 mS cm -1 The experimental results show that the effects of using FeCl3·6H2O and FeOCl synthesized from saturated FeCl3 solution as precursors to synthesize amorphous high ion conductivity cathode materials are similar, which makes the selection of the material synthesis route quite flexible and is conducive to further modification of the material in the future; Examples 2-3 show that near the appropriate reaction ratio, the ion conductivity of the obtained amorphous high ion conductivity cathode material can reach 0.1 mS cm -1 Level plays an important role in improving the capacity and rate performance of positive electrode materials.

[0103] The positive electrode materials prepared in Comparative Examples 1-4 were characterized by ionic conductivity using the blocking electrode method. The results are as follows: Figure 3The experimental results show that when the appropriate reaction ratio is exceeded or unsuitable ball milling reaction conditions are used, the ionic conductivity of the synthesized positive electrode material will be significantly reduced, and it cannot be used as a high ion conductivity positive electrode material without adding a supporting electrolyte.

[0104] Two chloride positive electrode materials Li3VCl6 and Li2FeCl4 were selected as comparative examples 5 and 6, and constant current charge and discharge tests were carried out. The charge and discharge curves are shown in FIG. Figure 4 At 0.1 mA cm -1 Example 1 can exert 408.8 mAh g -1 The specific capacity is significantly higher than that of Comparative Example 5 (163.1 mAh / g) and Comparative Example 6 (283.4 mAh / g), indicating that the amorphous high ion conductive cathode material has a high specific capacity, which is conducive to the construction of high energy density solid-state battery devices.

[0105] The cycle performance test of Example 1 was carried out, and the long cycle performance curve is as follows: Figure 5 At 0.5 mA cm -1 The current density is 1.0-4.2 V, and the charge and discharge cycle is carried out in the voltage range. The specific capacity of the positive electrode material is 226 mA h g -1 After 600 cycles, the capacity retention rate was 66.5%, showing good cycle performance.

[0106] The rate performance test of Examples 1-4 was carried out, and the results are as follows Figure 6 As shown in the figure, the positive electrode material Example 1 is at 2 mA cm -1 At a current density of 1.044 W, the capacity is 101.36 mA h g -1 , is 0.1 mA cm -1 32.6% under current density, indicating that it has good rate performance; Examples 2-3 also have excellent rate performance, indicating that the synthesis of the material has considerable flexibility in the selection of precursor synthesis method and raw material ratio.

[0107] After the humidity stability test of Example 1 was carried out, the ionic conductivity of the materials before and after exposure was characterized by the blocking electrode method. The results are as follows: Figure 7 The positive electrode materials of Example 1 before and after exposure were cold pressed and recorded as Example 1-1 and Example 1-2, respectively, with thicknesses of 0.34 mm and 0.43 mm, and corresponding resistance values ​​of 0.253 mS cm and 0.43 mS cm, respectively. -1 and 0.225 mS cm -1 The ion conductivity decreased by 11.1%. The XRD characterization results of the materials before and after exposure are as follows Figure 8As shown, the XRD spectra of the samples before and after exposure remain highly consistent, and no impurity phase is generated. In summary, the amorphous high ion conductivity cathode material has good humidity stability and can be synthesized in a common drying room for processing lithium metal, thereby reducing the requirements for hardware equipment updates during the production process.

Claims

1. A method for preparing an amorphous high ion conductive cathode material, characterized in that: The method comprises the following steps: Step 1, take FeCl3·6H2O or saturated FeCl3 aqueous solution and place it in a porcelain boat; Step 2, placing the porcelain boat in a muffle furnace, heating it to 200-230°C, keeping the temperature for a period of time, and then naturally cooling it to room temperature; Step 3, grinding the sample calcined in step 2, washing with a solvent and drying to obtain a FeOCl intermediate; Step 4, uniformly mixing the FeOCl intermediate obtained in step 3 with LiF; Step 5, adding the mixture of the FeOCl intermediate and LiF in step 4 into a ball milling jar and adding ball milling beads into the jar, and then sealing the ball milling jar to perform a high-energy ball milling reaction; Step 6, grinding the product obtained in step 5 to obtain the amorphous high ion conductive positive electrode material; Wherein, in step 5, the specific process of high-energy ball milling reaction is: ball milling speed 300-2000 rpm, ball milling reaction time 5-10 h; In step 4, LiF is used as the lithium source, FeOCl is used as the iron source, the molar ratio of LiF to FeOCl is y, and 0.1 <y<1。 2. The method for preparing an amorphous high ion conductive cathode material according to claim 1, characterized in that: In step 2, the heating rate is 3-5 °C / min and the holding time is 1.5-2 h; In step 3, the washing step includes two steps: water washing and organic solvent washing, and the selected organic solvent is one or a mixed solvent of two or more selected from methanol, ethanol, ether and acetone.

3. An amorphous high ion conductive positive electrode material prepared by the preparation method of claim 1, characterized in that: The positive electrode material is composed of five elements: lithium, iron, oxygen, chlorine and fluorine, and the general chemical composition formula is Li x FeOClF x , where x represents the molar ratio of Li and F relative to FeOCl, 0.1 <x<1。 4. The amorphous high ion conductive cathode material according to claim 3, characterized in that: 0.125<x<0.75。 5. An application of the amorphous high ion conductive positive electrode material according to claim 3 or 4, characterized in that: The positive electrode material is applied to an all-solid-state lithium-ion battery, has high lithium-ion conductivity and stable charge and discharge capability, and after being compounded with a conductive agent, can achieve stable operation in the all-solid-state lithium-ion battery at room temperature without adding a supporting electrolyte.

6. An all-solid-state lithium-ion battery composite positive electrode, characterized in that: The all-solid-state lithium-ion battery positive electrode comprises the amorphous high ion conductive positive electrode material according to claim 4 or 5 and a conductive agent.

7. The composite positive electrode according to claim 6, characterized in that: The conductive agent is one or more of carbon nanotubes, carbon nanofibers, graphene, Ketjen black, acetylene black, and activated carbon, and the mass of the conductive agent accounts for 5-10% of the total mass of the composite positive electrode.

8. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the all-solid-state lithium-ion battery composite positive electrode according to claim 6 or 7.

9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The all-solid-state lithium-ion battery also includes a solid electrolyte and a negative electrode; The solid electrolyte is a double-layer electrolyte composed of Li2ZrCl6 and Li6PS5Cl, and the negative electrode is a lithium metal foil or a lithium indium alloy foil.

Citation Information

Patent Citations

  • Nano-composite electrode material for chloride ion battery and preparation method of material

    CN107331838A

  • Preparation method of high-ionic-conductivity amorphous oxyhalide solid electrolyte

    CN118136933A